PERAN GANDA PEREMPUAN DALAM KELUARGA DITINJAU DARI PERSPEKTIF GENDER (Studi Terhadap Pedagang Sayur di Poken Jonjong Pijorkoling) - Kholidah Kholidah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Abstract: The involvement of women vegetable traders in â€œpoken Jonjongâ€ to make a living for their family add their working hours. It happen because they earn a living in one side, and they are also expected to play a role as a housewife in other side, which is in charge of doing the whole job domestically. Time usage patterns and activities for domestic affairs, employment, social activities and the utilization of spare time, are set in such a way. They manage the time as best as possible and adapt to the environmental component of family, work and community environment with the intention that the family welfare objectives can be achieved. The women vegetable traders in Poken Jonjong, generally decide to contribute for a living (double play) because of economic factors. The traders contributes substantially to the increase in family income. This can be seen from the fulfillment of daily needs in the household, the children can study though only at the level of Senior High School and there are of the traders that can save their money. Kata Kunci: Peran Ganda, Perempuan, Perspektif Gender